Degenerative processes in bioprosthetic mitral valves in juvenile pigs - Pedersen Torben B; Funder Jonas A; Honge Jesper L; Kronborg Mads B; Hasenkam J Michael (Journal of Cardiothoracic Surgery, 2011)
Abstract Background Glutaraldehyde-treated bioprosthetic heart valves are commonly used for replacement of diseased heart valves. However, calcification and wear limit their durability, and the development of new and improved bioprosthetic valve designs is needed and must be evaluated in a reliable animal model. We studied glutaraldehyde-treated valves 6 months after implantation to evaluate bioprosthetic valve complications in the mitral position in juvenile pigs. Materials The study material comprised eight, 5-month old, 60-kg pigs. All pigs received a size 27, glutaraldehyde-treated, stented, Carpentier-Edwards S.A.V. mitral valve prosthesis. After six months, echocardiography was performed, and the valves explanted for gross examination, high resolution X-ray, and histological evaluation. Results Five pigs survived the follow-up period. Preexplant echocardiography revealed a median peak and mean velocity of 1.61 m/s (range: 1.17-2.00) and 1.20 (SD = ±0.25), respectively, and a median peak and mean pressure difference of 10.42 mmHg (range: 5.83-16.55) and 6.51 mmHg (SD = ±2.57), respectively. Gross examination showed minor thrombotic depositions at two commissures in two valves and at all three commissures in three valves. High resolution X-ray imaging revealed different degrees of calcification in all explanted valves, primarily in the commissural and belly areas. In all valves, histological evaluation demonstrated various degrees of fibrous sheath formation, limited immunological infiltration, and no overgrowth of host endothelium. Conclusions Bioprosthetic glutaraldehyde-treated mitral valves can be implanted into the mitral position in pigs and function after 6 months. Echocardiographic data, calcification, and histological examinations were comparable to results obtained in sheep models and human demonstrating the suitability of the porcine model.